Educating Consumer Awareness on Halal Issues: A Case Study of Viral Products Mixue and Ai-Cha in Malaysia - Nur Amalina; Normarlina (CV Najmi Edu Creative, 2025)
This qualitative study explores the rise of viral beverage brands Mixue (China) and Ai-Cha (Indonesia) among Malaysian Muslim consumers, focusing on the implications of their uncertified halal status. Despite Malaysia’s comprehensive halal certification system governed by JAKIM, many consumers—especially youth—exhibit limited awareness and verification practices regarding halal compliance. This study aims to assess halal literacy, identify behavioral gaps, and propose educational strategies to address syubhah (doubtful) consumption. Using document-based content analysis of official guidelines (MS1500:2019), Islamic jurisprudence, media discourse, and consumer behavior literature, findings indicate that brand aesthetics, social media influence, and pricing often outweigh religious considerations. The results underscore an attitude-behavior gap, where consumers affirm halal values but do not consistently act on them. The study concludes that enhanced formal and informal halal education, particularly among youth, is critical to strengthening faith-aligned consumption. Recommendations include multi-platform public outreach and curriculum integration to foster informed, ethical, and faith-conscious consumer behavior.